STUDI TERHADAP PENGELOLAAN HARTA NEGARA MENURUT PERSPEKTIF EKONOMI ISLAM DAN PENERAPANNYA DI NDONESIA - Febriani, Winda; Taufiq, Muhammad (Jurnal Riset Rumpun Ilmu Ekonomi, 2022)
This study aims to analyze and evaluate the management of public ownership (milkiyah 'ammah) and state ownership (milkiyah daulah) in Indonesia. This study describes in a qualitative descriptive way the current management of public ownership and state ownership in Indonesia. The theoretical approach is used for the Islamic economic system approach which assesses the practical implementation of the management of shared wealth and the wealth of the Indonesian State. The data used in this study are secondary data obtained from literature, journals and information related to Indonesia's wealth. The data collection technique used is library research. And this study uses a comparative analysis of the implementation of public ownership management and state ownership management that is not in accordance with ownership management in Islam. Evidence shows that public ownership and state ownership are not fully managed by the State of Indonesia, it appears that shared ownership in the form of water, fire and pasture is managed by individuals and institutions of foreign parties who have the capital to privatize public ownership. This will have an impact on the unequal distribution of income earned by people who have capital and those who do not have capital, so that it will have an impact on prosperity that most Indonesian people cannot have. As an evaluation and solution, it is necessary to implement an Islamic economic system in managing joint ownership and control of the Indonesian state.